Thesis Report for the Design and Qualification of a Modular Scientific Drone - Borrageiro, Mauro (Department of Electrical Engineering, 2024)
Data acquisition using small unmanned aircraft systems (sUAS) or drones for scientific research purposes continues to grow as a new norm across a wide spectrum of disciplines. Consumer sUAS often boast high quality stabilised video capture capabilities and easy-to-use platforms. However, given the need for stringent data provenance and rigour in scientific data capture processes, these platforms are often limiting for academic research purposes due to closed source firmware and communication links, thus requiring sensor and mechanical infrastructure duplication on deployed platforms. This paper presents the LANDRS open source Modular Science Drone; an open source flexible multirotor design, intended to provide the high quality and easy user experience of consumer platforms in a form that enables advantageous tight integration of custom sensors with full access to necessary data and metadata capture process provenance. The Science Drone was designed to operate as either a quadcopter or hexacopter for greater accessibility and versatility, with an operational flight time in the range of 15 to 20 minutes and the ability to lift a 5kg payload. The design used readily available components to configure the powertrain, command and control and power subsystems. The structural frame of the drone was designed and qualified in CAD simulation software with an e↵ort to use simple manufacturing techniques such as 3D printing. The result was a simple to use, easy to replicate, and well documented drone focused on accessibility for research. The presented design was performance tested and validated in a number of typically expected flight behaviours for scientific research drones to determine the endurance and heavy lift capabilities compared to literature referenced commercial and custom drones. The dissertation that follows outlines the design decisions and verification methods for the overall multirotor system and associated subsystems. It subsequently, reports the performance results of the quad- and hexacopter configurations in comparison to the set-out requirements before concluding with suggested future work.